ASPECTS OF BUSINESS PLANNING FOR THE DEVELOPMENT OF HOTEL AND RESTAURANT BUSINESS ENTITIES (Development Service Industry Management, 2025)
The article develops a set of solutions and proposals related to the management of the development of hotel and restaurant entities. It is indicated that the hotel and restaurant business requires careful planning, especially with the use of such a tool as business planning. Therefore, the purpose of the study is to generalize and further develop methodological and applied provisions and aspects of business planning for the development of hotel and restaurant entities. It is argued that the use of business planning allows you to plan all aspects of the future business, respectively, to organize it with optimal time and financial costs, to anticipate challenges, risks and threats and implement timely measures to prevent and eliminate them. However, business planning tools should be used even after the creation and a certain stage of development of a business entity. That is why a description of the practice of applying business planning, in particular strategic planning for the development of a business unit, is provided, The article studies the hotel and restaurant enterprise. SWOT analysis of the external and internal environment of the hotel and restaurant entities has been applied. Methodological aspects of modeling the volume of economic activity in business planning for the development of the enterprise have been developed. The factors that should be taken into account during business planning for the development of hotel and restaurant entities are indicated. The scientific novelty of the research results lies in the further development of methodological recommendations for business planning for the development of existing hotel and restaurant entities, based on strategic business analysis and the development of individual elements of a new business growth plan. The applied significance of the research results lies in the use of the developed recommendations for the purpose of more thorough planning, and, consequently, effective development of the hotel and restaurant business entities.
Keywords: business; enterprise; business entity; management; business processes; business planning; hotel and restaurant business; development